Ultrasound-Guided Percutaneous Ethanol-Paclitaxel Combined Therapy for Rabbit VX2 Liver Tumors - Chen L; Liu ZX; Bi QC; Zhao J; Liang QR; Tang Q (Journal of Hepatocellular Carcinoma, 2021)
Li Chen,1 Zhi-xing Liu,1 Qiu-chen Bi,2 Jun Zhao,3 Qing-rong Liang,2 Qun Tang2– 4 1Department of Ultrasonic Radiology, The First Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China; 2Institute for Advanced Study, Nanchang University, Nanchang, People’s Republic of China; 3Jiangxi Provincial Key Laboratory of Preventive Medicine, School of Public Health, Nanchang University, Nanchang, People’s Republic of China; 4Jiangxi Province Key Laboratory of Laboratory Animal, Nanchang, People’s Republic of ChinaCorrespondence: Qun TangJiangxi Provincial Key Laboratory of Preventive Medicine, School of Public Health, Nanchang University, Xuefu Avenue No. 999, Honggutan District, Nanchang, 330031, People’s Republic of ChinaTel/Fax +86 791-83969963Email tangqun@ncu.edu.cnBackground: It is difficult to achieve whole tumor ablation using percutaneous ethanol ablation therapy (PEAT) due to the limited diffusion of ethanol.Purpose: To determine whether chemotherapy can be an adjuvant therapy to benefit PEAT, we investigated ultrasound-guided percutaneous ethanol-paclitaxel combined therapy (PEPCT) of VX2 carcinoma, a rabbit liver cancer model.Materials and Methods: A six-arm study was designed to quantify the correlation between paclitaxel (PTX) dose and tumor necrosis or cell proliferation, including sham group (2 mL saline, n=6), incremented dose of PTX (0, 12.5, 25, 37.5 mg) in 2.0 mL ethanol (n=6) and a conventional PEAT group (n=6) as comparison. The test was followed by contrast-enhanced ultrasonic (CEUS) before 7-day sacrifice, tumor harvest, and sectioning. Tumor necrosis ratio was radiologically and histologically quantified; modified proliferation index (m-PI) was proposed to quantify the PTX’s pharmacological effects. A linear regression model was set to correlate the PTX dose with tumor necrosis ratio or cell proliferation index. The difference of radiological, histological necrosis ratio (HNR) and modified PI in six groups was analyzed via Kruskal–Wallis H-test, Welch analysis of variance and one-way ANOVA.Results: Incremental increases of PTX (0, 12.5, 25, 37.5 mg) correlated with greater fraction of tumor necrosis (R2 = 0.946, P< 0.001 for radiological necrosis ratio [RNR], R2 = 0.843, P< 0.001 forHNR), indicating that one week after procedure PTX’s anti-proliferation and ethanol’s dehydration co-induced severe tumor necrosis. Correlation analysis further testified a significant association between PTX dose and m-PI (R2 = 0.860, P< 0.001).Conclusion: These results suggest a clear role for PTX-induced cytotoxicity and support the use of chemotherapeutic drugs in ablation therapy.Keywords: percutaneous ethanol ablation therapy, PEAT, paclitaxel, PTX, new indication, combined therapy, VX2 liver cancer model